Directions: Using the digits 1 to 9, at most one time each, fill in the boxes so that the two functions are equivalent

### Hint

### Hint

How do you use function notation to determine the input and output of a function?

### Answer

### Answer

One possible answer is:

f(x) = 9x + 4

g(x) = 7x^2 – 1x + 5

f(3) = g(2)

f(x) = 9x + 4

g(x) = 7x^2 – 1x + 5

f(3) = g(2)

Post any others in the comments.

Source: Steven Midzak

I think the format is confusing, and the answer uses incorrect notation and the two functions are, in fact, never “equivalent”. Rephrase like this?

Fill in spaces with whole numbers 1 – 9 only one time, so that the final equality is correct.

f(x) = ___ x + _____

g(x) = ___ x^2 – ____x + _____

f(____) = g(_____)

I agree. I like the format you used better Tim.

Thank you for this suggestion. I’ve edited the question accordingly.

It doesn’t appear to be edited.

f(3) = 2x + 4

g(1) = 7x^2 – 6x + 9

F(3)=9x+4 g(2)=7x^2-1x+5

f(9)=1x+3

g(2)=4x^2-5x+6

𝑓(3)=7𝑥+6 𝑔(2)=5𝑥^2−1𝑥+9

𝑓(8)=6𝑥+4 𝑔(5)=2𝑥^2−1𝑥+7

I gave this to my IM3 classes today, here are some they came up with that are NOT listed above:

f(3) = 6x + 1 g(4) = 2x^2 – 5x + 7

f(8) = 2x + 3 g(6) = 1x^2 – 4x + 7

f(1) = 3x + 6 g(2) = 4x^2 – 8x + 9

f(2) = 3x + 4 g(1) = 7x^2 – 5x + 8

f(2) = 3x + 7 g(5) = 1x^2 – 4x + 8

I should have looked at the solutions earlier. That negative before the x term in the quadratic makes all the difference as per Tim’s comment waaaaay back. I wonder why the question as posted still shows the +.

Thank you for this site, it is awesome!

f(x) = 8x + 5; g(x) = 3x^2-x+9

f(6) = g(4) = 53